Betanodavirus-like particles enter host cells via clathrin-mediated endocytosis in a cholesterol-, pH- and cytoskeleton-dependent manner. (January 2018) - Huang, Runqing; Zhu, Guohua; Zhang, Jing; Lai, Yuxiong; Xu, Yu; He, Jianguo; Xie, Junfeng
Abstract Betanodavirus, also referred to nervous necrosis virus (NNV), is the causative agent of the fatal disease, viral nervous necrosis and has brought significant economic losses in marine and freshwater cultured fish, especially larvae and juveniles. Here, we used an established invasion model with virus-like particle (VLP)-cells, mimicking orange-spotted grouper nervous necrosis virus (OGNNV), to investigate the crucial events of virus entry. VLP were observed in the perinuclear regions of Asian sea bass (SB) cells within 1.5 h after attachment. VLP uptake was strongly inhibited when cells were pretreated with biochemical inhibitors (chlorpromazine and dynasore) blocking clathrin-mediated endocytosis (CME) or transfected with siRNA against clathrin heavy and light chains. Inhibitors against key regulators of caveolae/raft-dependent endocytosis and macropinocytosis had no effect on VLP uptake. In contrast, disruption of cellular cholesterol by methyl-β-cyclodextrin or reduction of cholesterol fluidity by Cholera toxin B subunit significantly decreased VLP entry. Furthermore, VLP entry is dependent on low pH and cytoskeleton, demonstrated by inhibitor (chloroquine, ammonia chloride, cytochalasin D, wiskostatin, and nocodazole) perturbation. Therefore, OGNNV VLP enter SB cells via CME depending on dynamin-2, cholesterol and its fluidity, low pH, and cytoskeleton. In addition, ten more cell lines were screened for VLP entry and VLP can only enter NNV-sensitive cells, GB and SSN-1, via CME, indicating that CME is the common endocytosis pathway for VLP. These results may provide the data for NNV entry without the influence of the viral genome, an ideal model for exploring the behaviour of betanodavirus in cells, and valuable references to vaccine development.